Vinegar-Preserved Sea Fennel: Chemistry, Color, Texture, Aroma, and Taste - Sanja Radman; Petra Brzović; Mira Radunić; Ante Rako; Mladenka Šarolić; Tonka Ninčević Runjić; Branimir Urlić; Ivana Generalić Mekinić (Foods, 2023)
The aim of this study was to produce non-fermented preserved sea fennel leaves in different pickle juices prepared with apple cider vinegar, wine vinegar and alcoholic vinegar, and to compare their chemical parameters (pH, titratable acidity and salt content), organoleptic properties (color and texture parameters; volatile aromatic compound profiles) and sensory attributes. The pH of the samples ranged from 3.49 to 3.64, the lowest being in the alcoholic vinegar sample and the highest being in the wine vinegar sample, while the titratable acidity and salinity were higher in the alcoholic vinegar pickle juice than those in the other two samples. The volatile aromatic compounds of the samples were also detected. The reddish color of the wine vinegar negatively affected the sea fennel color parameters (L* and b*), and was also negatively evaluated by the panelists, while the alcoholic vinegar maximally preserved the green tones of the leaf (a*). Firmness influences the quality perceived by consumers and was therefore also tested as one of the most important parameters for evaluating the textural and mechanical properties of the different products. All sensory parameters of the sea fennel preserved in alcoholic vinegar, namely color, texture, taste, aroma and overall impression, were given the highest scores, while the sample preserved in wine vinegar received the lowest scores. The intense aroma of the wine vinegar was described as a negative characteristic (off-flavor) of the sample.